Adolescent fertility and family planning in East Asia and the Pacific: a review of DHS reports - Gray Natalie; Kennedy Elissa; Azzopardi Peter; Creati Mick (BMC, 2011)
Abstract Background Adolescent pregnancy has significant health and socio-economic consequences for women, their families and communities. Efforts to prevent too-early pregnancy rely on accurate information about adolescents' knowledge, behaviours and access to family planning, however available data are limited in some settings. Demographic and Health Survey (DHS) reports are recognised as providing nationally representative data that are accessible to policymakers and programmers. This paper reviews DHS reports for low and lower middle income countries in East Asia and the Pacific to determine what information regarding adolescent fertility and family planning is available, and summarises key findings. Methods The most recent DHS reports were sought for the 33 low and lower middle income countries in the East Asia and Pacific region as defined by UNICEF and World Bank. Age-disaggregated data for all indicators relevant to fertility and current use, knowledge and access to family planning information and services were sought to identify accessible information. Reported data were analysed using an Excel database to determine outcomes for adolescents and compare with adult women. Results DHS reports were available for eleven countries: Cambodia, Indonesia, Marshall Islands, Nauru, Papua New Guinea, Philippines, Samoa, Solomon Islands, Timor-Leste, Tuvalu and Vietnam. Twenty seven of 40 relevant DHS indicators reported outcomes for adolescent women aged 15-19 years. There were limited data for unmarried adolescents. A significant proportion of women commence sexual activity and childbearing during adolescence in the context of low contraceptive prevalence and high unmet need for contraception. Adolescent women have lower use of contraception, poorer knowledge of family planning and less access to information and services than adult women. Conclusion DHS reports provide useful and accessible data, however, they are limited by the failure to report data for unmarried adolescents and report age-disaggregated data for some indicators. Further research is required to better understand the barriers that both married and unmarried adolescents face accessing reproductive health information and services, and their information and service delivery preferences.